Soccer-specific endurance and running economy in soccer players with cerebral palsy - Kloyiam, S.; Breen, S.; Jakeman, P.; Conway, J.; Hutzler, Y. (Adapted Physical Activity Quarterly, 2011)
The purpose of this study was to describe running economy, soccer specific endurance, and selected kinematic running criteria in soccer players with cerebral palsy (SPCP) and to compare them with values of position-matched players without CP. Fourteen international, male soccer players with cerebral palsy completed the "Yo-Yo" intermittent recovery run level 1 (IRL-1) test to assess soccer-specific endurance and a submaximal running test on a treadmill to determine running economy. The mean IRL-1 distance covered by the SPCP of the Irish CP team was found to be 43-50% below the mean distance attained by position-matched soccer players without disability, while running economy was found to be within the range of that reported for able-bodied athletes. No relationship could be found between the level of CP-ISRA classification and soccer-specific endurance or running economy in this group of elite level SPCP. Though small in number, these data support a further examination of the relationship between CP classification and sport-specific performance.